Щодо методології дослідження системи джерел цивільного права України - Дрішлюк, Андрій Ігорович; Дришлюк, Андрей Игоревич; Drishljuk, Andrej (My University, 2013)
The article is devoted to the question to forming of methodological base for realization of research of the system of sources of civil law of Ukraine, to the decision of basic directions of their research, and also separate aspects of rich in content character.
Дрішлюк А. І. Щодо методології дослідження системи джерел цивільного права України / А. І. Дрішлюк // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 479-489.
Keywords: джерело права; система джерел цивільного права України; методологія; методи дослідження; діалектика; источник права; система источников гражданского права Украины; методология; методы исследования; диалектика; source of law; system of sources of civil law of Ukraine; methodology; methods of research; dialectician